Comparison of Models for 3D Printing of Solitary Fibrous Tumor Obtained Using Open-Source Segmentation Software - Tincopa, Jean Pierre (2022)
“The objective of the present study is to make a comparison between various free and open-source software used for medical image processing, such as 3D Slicer (version 4.11), ITK-Snap (version 3.8), and Invesalius (version 3.1) in its application for the calculation of solitary fibrous tumor volumes. Knowing the size, shape, and volume of mesothelioma is decisive for clinical decisionmaking by health personnel when performing surgery; the currently used standard procedure is manual segmentation through magnetic resonance imaging (MRI). This process tends to take a long time to complete. On the other hand, automatic segmentation software is much faster and more user-friendly, so looking for software that gives us greater accuracy when doing this task is very important. This work obtained magnetic resonance imaging (MRI) of a mesothelioma patient, and the images were segmented in the 3 different programs to evaluate the concordance between the software later.“